2012
DOI: 10.1134/s207511331103018x
|View full text |Cite
|
Sign up to set email alerts
|

Technological characteristics of the processes of carbon nanostructure production by the methods of plasma-arc and gas-pyrolytic deposition

Abstract: The techniques of pyrolytic vapor deposition from acetylene and plasma arc vacuum deposition of graphite are used to prepare carbon nanotubes (CNTs). Graphite electrodes for plasma arc deposition are premodified with transition metals by electrochemical deposition from aqueous solutions of their salts. It is shown by SEM and AFM that the structure and morphology of the surface of CNT samples depends on the synthesis technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…3; the following notation was used in the figure: ER is epoxy resin; ER/TNC is epoxy resin with Taunit com mercial nanotubes [14]; ER/CPD ENTs is epoxy resin with unaligned catalytic pyrolysis deposition entangled nanotubes [15,16]; ER/HANTs is epoxy resin with horizontally aligned nanotubes; ER/VANTs is epoxy resin with VANTs; and VANTs is a VANT array.…”
Section: Resultsmentioning
confidence: 99%
“…3; the following notation was used in the figure: ER is epoxy resin; ER/TNC is epoxy resin with Taunit com mercial nanotubes [14]; ER/CPD ENTs is epoxy resin with unaligned catalytic pyrolysis deposition entangled nanotubes [15,16]; ER/HANTs is epoxy resin with horizontally aligned nanotubes; ER/VANTs is epoxy resin with VANTs; and VANTs is a VANT array.…”
Section: Resultsmentioning
confidence: 99%
“…Our SEM inspection showed that TNC-powder composed of very entangled and branching nanotubes conglomerated in micron-sized ball-like particles with a significant (up to 20%) amorphous fraction. The setup for VANTs growth has been described previously [27]. Schematically, it was a quartz tube of about 1" in diameter placed in an automatically temperature controlled oven with an automatically controlled flow rates of buffer gas (N 2 ).…”
Section: Cnts Synthesismentioning
confidence: 99%